PENGARUH PEMBERIAN PUPUK BIO -SLURRY TERHADAP PERTUMBUHAN VEGETATIF TANAMAN SAWI HIJAU (Brassica juncea L.) - M IDRIS MP (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the effect of bio-slurry fertilizer application on the vegetative growth of green mustard plant (Brassica juncea l.)The research was conducted at Jalan Karya Kasih, Gang sawah, Medan Johor Sub-district, Medan at least ± 30 m above sea level. The research was conducted from June 2020 to July 2020.The materials used in this study were green mustard seeds, top soil taken from the from Medan Johor sub-district, Medan City, Manure in the form of cow dung and goat manure which were used as basic ingredients for bio-Sllury and M-Bio fertilizers as pro- biotok for making Bio-Sllury compost and 10 kg polybags.There are lots of tools such as Hands prayer s, hoes, machetes, chainsaws, title boards, plot boards and treatment boards, speed and stationeryThis study used a factorial randomized design consisting of 2 factors and 3 replications, namely: Factor I. Bio-Slurry fertilizer from cow dung (L), consisting of three levels, namely; L0 = Without Application of Cow Manure = 0 ton/ha or 0 g/Polybag ; L1 = 10 tons/ha or 40 g/Polybag; L2 = 20 ton/ha or 80 g/Polybag . Factor II. Bio-Slurry Fertilizer from Goat Manure (K) which consists of three levels, namely; K0 = Without Goat Manure = 0 ton/ha or 0 g/Polybag ; K1 = 10 tons/ha or 40 g/Polybag; K2 = 20 ton/ha or 80 g/Polybag . Thus there are 9 treatment combinations. 3 replicates and 27 polybag.The implementation of the research includes: soil preparation, planting seeds, fertilization and harvesting while plant maintenance includes: insertion, giving water, weeding and controlling pests and disease.Observation variables include: plant height (cm), number of leaves (strands), and wet weight (g). Furthermore, if the results of the research test show a significant difference from the treatment being tried, it can be continued with the Honest Average Difference (DMRT) test method.